121k views
4 votes
A, B, and C are polynomials, where:

A = 3x – 4
B = x + 7
C = x2 + 2
What is A2 – (B + C) in simplest form?
A. 8x2 – 25x + 7
B .8x2– 25x + 11
C. 10x2 – 25x + 7
D. 10x2 – 25x + 11

User Dsyko
by
6.1k points

2 Answers

4 votes

Answer:

A

Explanation:

edge2020

User Luke Taylor
by
5.8k points
3 votes

Answer:

Option A. 8x² - 25x + 7.

Explanation:

The given polynomials are

A = 3x -4

B = x + 7

C = x² + 2

Now we have to find the simplest form of A² - (B + C)

A² = (3x - 4)² = 9x² + 16 -24 x

B + C = x + 7 + x² + 2 = x² + x + 9

Now A² - (B + C) = 9x² + 16 -24x -(x² + x + 9)

= 9x² -24x + 16 - x²- x - 9

= 8x² -25x + 7

Therefore Option A. 8x² - 25x + 7 is the answer.

User Clea
by
6.2k points